Role FtsH4 proteázy při adaptaci na environmentální stres - Novotná, Kateřina (Jihočeská univerzita, 2022)
FtsH proteases are membrane-embedded proteolytic complexes important for protein quality control and regulation of various physiological processes in bacteria, mitochondria and chloroplasts. Most cyanobacteria, including the model species Synechocystis sp. PCC 6803, contain four FtsH homologues, FtsH1-FtsH4. FtsH1-3 form two hetero-oligomeric complexes, FtsH1/3 and FtsH2/3 that play an important role in acclimation to nutrient deficiency and photosystem II (PSII) quality control, respectively. FtsH4 differs from the other three homologs by the formation of a homo-oligomeric complex. The role of this complex remained unknown. To reveal the function of FtsH4 protease, we characterized mutants lacking and over-expressing the ftsH4 gene, under various stress conditions. Our results revealed that FtsH4 participates in transition to stationary phase. The excess of FtsH4 protein slows down the transition. In addition, FtsH4 plays an important role in short- and long-term acclimation to high light stress, especially after dilution from stationary phase. After short-term high light exposition, FtsH4 contributes to faster cell growth, presumably by promoting the expression of proteins required for acclimation to the stress. After long-term exposition to high light, it regulates the level of HliD protein which is important for protection and hence stabilization of PSII complex. Our results also indicate that FtsH4 is implicated in a regulation of carbon metabolism.
The role of FtsH4 protease during adaptation to environmental stress